6. The Faculty of Chemical Sciences and the Mexican Chemical Society, 1926-1933 - Pastrana, Patricia Aceves; Solis, Sandra Martínez (Circumscribere International Journal for the History of Science, 2008)
This paper deals with the foundation in 1926 of Mexican Chemical Society; the goals guiding it and its main protagonists, through the analysis of its informative publication, Revista Química (Chemical Journal). In this way it is sought to highlight the role of this Society in the organization of Mexican chemists and the construction of the identity of the emerging chemical professions.